Effectiveness of Modified Learning Media on Student Creativity - Akin, Yogi; Suherman, Ayi; Safari, Indra; Susilawati, Dewi; Sudrazat, Adang; Nugraha, Reshandi; Brilian, Mohamad (Universitas Pendidikan Indonesia, 2023)
This study aimed to determine the influence of modified learning media on the student creativity. The research method employed an experimental method with a pretest-posttest control group design. The sample of this study consisted of PETE for Elementary School students selected through purposive sampling. The research instrument utilized a creativity questionnaire. Based on the data analysis, the significance value was 0.019, indicating a significant influence of modified learning media on the student creativity. This study concludes that there was a significant impact of modified learning media on the student creativity. Modifying learning media can be considered a viable alternative in education to enhance creativity and other cognitive components.